2021
DOI: 10.48550/arxiv.2103.00011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Error-correction properties of an interacting topological insulator

Abstract: We analyze the phase diagram of a topological insulator model including antiferromagnetic interactions in the form of an extended Su-Schrieffer Heeger model. To this end, we employ a recently introduced operational definition of topological order based on the ability of a system to perform topological error correction. We show that the necessary error correction statistics can be obtained efficiently using a Monte-Carlo sampling of a matrix product state representation of the ground state wave function. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The antiferromagnetic order computed using the DNN in Fig. 2(c) is in strong agreement with the phase diagram established using other methods 17,22 . Hence, we have demonstrated that a DNN trained with a certain perturbation of the reference state is capable of detecting the gapped phase in the presence of different perturbations.…”
Section: Extended Bosonic Ssh Modelsupporting
confidence: 85%
See 4 more Smart Citations
“…The antiferromagnetic order computed using the DNN in Fig. 2(c) is in strong agreement with the phase diagram established using other methods 17,22 . Hence, we have demonstrated that a DNN trained with a certain perturbation of the reference state is capable of detecting the gapped phase in the presence of different perturbations.…”
Section: Extended Bosonic Ssh Modelsupporting
confidence: 85%
“…In the following, we introduce our method to detect gapped quantum phases, which is inspired by the operational definition for topological order 16 . We therefore briefly review this approach and extensions to phases exhibiting local order 17 . Essentially, this operational definition interprets topological order as the intrinsic ability of a system to perform topological error correction and classifies topological phases in terms of reference states without any errors.…”
Section: Learning From the Operational Definition Of Topological Ordermentioning
confidence: 99%
See 3 more Smart Citations